In Vitro Evaluation of Antimicrobial Effect of Phytobiotics Mixture on Salmonella spp. Isolated from Chicken Broiler - Hubert Iwiński; Karolina Wódz; Karolina Chodkowska; Tomasz Nowak; Henryk Różański (MDPI AG, 2022)
Background: The identification of natural antibacterial agents from various sources that can act effectively against disease-causing foodborne bacteria is one of the major concerns throughout the world. In the present study, a unique phytobiotics mixture containing thymol, menthol, linalool, trans-anethole, methyl salicylate, 1,8-cineole, and p-cymene was evaluated for antibacterial activity against selected strains of Salmonella spp. Results: The phytobiotics mixture was effective against Salmonella enterica subsp. enterica serovars Enteritidis, Typhimurium, and Kentucky. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of this unique mixture for these three pathogens were 1:256. Among these three strains, one S. Kentucky presented the most extensive resistance profiles to 18 antibiotics belonging to 5 classes of antibiotics. One of S. Typhimurium presents extensive resistance profiles to 14 antibiotics belonging to 5 classes of antibiotics. Conclusions: The results suggest that the phytobiotics mixture used in the experiment can be used as a strong natural antibacterial agent against Gram-negative foodborne pathogens such as S. Typhimurium, S. Kentucky, and S. Enteritidis. This is a preliminary analysis of the effectiveness of a phytobiotic product in an in vitro model, which may be the starting point for further studies, including in vivo animal models.